THE INFLUENCE OF SELF EFFICACY AND LOCUS OF CONTROL ON EMPLOYEE PERFORMANCE AT PT.GUARDIAN PHARMATAMA MEDAN BRANCH - Indriani Adha; Anggia Sari Lubis; Wan Dian Safina; Horia Siregar (Universitas Efarina, 2024)
The purpose of this study was to determine and analyze the effect of self-efficacy and locus of control on employee performance at PT Guardian Pharmatama Medan Branch. This type of research is Quantitative. This study involved employees at Pt. Guardian Pharmatama Medan Branch as many as 41 people. This study used a saturated sample, so the sample in this study used all 41 people. Data collection techniques in this study were observation, documentation and questionnaires with a Likert Scale data measurement scale. Data analysis techniques use validity, reliability and classical assumption tests. The data analysis method uses multiple linear regression with the help of the SPSS program. The results of the study prove that Self Efficacy has a positive and significant effect on employee performance. Locus Of Control has a positive and significant effect on employee performance. Simultaneously the results of Self Efficacy and Locus Of Control have a positive and significant effect on employee performance at PT Guardian Pharmatama Medan Branch.